Development of a Loop-Mediated Isothermal Amplification Method for Detection of Histoplasma capsulatum DNA in Clinical Samples - Scheel, Christina M.; Zhou, Yitian; Theodoro, Raquel C. [UNESP]; Abrams, Bethany; Balajee, S. Arunmozhi; Litvintseva, Anastasia P. (Amer Soc Microbiology, 2014)
Improved methods for the detection of Histoplasma capsulatum are needed in regions with limited resources in which the organism is endemic, where delayed diagnosis of progressive disseminated histoplasmosis (PDH) results in high mortality rates. We have investigated the use of a loop-mediated isothermal amplification (LAMP) assay to facilitate rapid inexpensive molecular diagnosis of this disease. Primers for LAMP were designed to amplify the Hcp100 locus of H. capsulatum. The sensitivity and limit of detection were evaluated using DNA extracted from 91 clinical isolates of known geographic subspecies, while the assay specificity was determined using DNA extracted from 50 other fungi and Mycobacterium tuberculosis. Urine specimens (n = 6) collected from HIV-positive individuals with culture- and antigen-proven histoplasmosis were evaluated using the LAMP assay. Specimens from healthy persons (n = 10) without evidence of histoplasmosis were used as assay controls. The Hcp100 LAMP assay was 100% sensitive and specific when tested with DNA extracted from culture isolates. The median limit of detection was <= 6 genomes (range, 1 to 300 genomes) for all except one geographic subspecies. The LAMP assay detected Hcp100 in 67% of antigen-positive urine specimens (4/6 specimens), and results were negative for Hcp100 in all healthy control urine specimens. We have shown that the Hcp100 LAMP assay is a rapid affordable assay that can be used to expedite culture confirmation of H. capsulatum in regions in which PDH is endemic. Further, our results indicate proof of the concept that the assay can be used to detect Histoplasma DNA in urine. Further evaluation of this assay using body fluid samples from a larger patient population is warranted.